2020
DOI: 10.1021/jacs.9b10086
|View full text |Cite
|
Sign up to set email alerts
|

Sungeidines from a Non-canonical Enediyne Biosynthetic Pathway

Abstract: We report the genome-guided discovery of sungeidines, a class of microbial secondary metabolites with unique structural features. Despite evolutionary relationships with dynemicin-type enediynes, the sungeidines are produced by a biosynthetic gene cluster (BGC) that exhibits distinct differences from known enediyne BGCs. Our studies suggest that the sungeidines are assembled from two octaketide chains that are processed differently than those of the dynemicin-type enediynes. The biosynthesis also involves a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…The structure of compound A was established by X-ray crystallography as 15-deoxy DYN A (8). 12 In addition to compound 1, a few DYN A congeners, namely DYN L (9), M (10) and N (11), 38 and O (12), P (13) and Q (14), 39 were also isolated from the fermentation broth of M. chersina. Treatment of DYN A with methyl thioglycolate generated DYN H (15) and DYN S (16).…”
Section: Discovery Of Afesmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of compound A was established by X-ray crystallography as 15-deoxy DYN A (8). 12 In addition to compound 1, a few DYN A congeners, namely DYN L (9), M (10) and N (11), 38 and O (12), P (13) and Q (14), 39 were also isolated from the fermentation broth of M. chersina. Treatment of DYN A with methyl thioglycolate generated DYN H (15) and DYN S (16).…”
Section: Discovery Of Afesmentioning
confidence: 99%
“…MD118. 10 Although the sungeidines were not isolated in the enediyne form, the comparison of their BGC with other known BGCs for AFEs suggested that the sungeidine pathway is closely related to the other AFE pathways. 11 The structures of the representative enediynes and the AFEs, i.e., DYN A (1), UCM (2), TNM A (3), YPM A (4), sealutomicin A (5) and sungeidine A (6) are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Chinese group applied comparative genomic and transcriptomic analyses to the resurrection efforts of the plant Selaginella tamariscina and revealed genetic mechanisms of drought tolerance in plants 65 . Similar multi‐omics approaches also led to the discovery of novel biosynthetic pathways from microbes isolated from Singapore's native environment, 66,67 as well as silent secondary metabolites in Streptomyces species 68 . Such novel discoveries not only add to our understanding of the biological systems, but also enrich the available molecular tools for synthetic biology research and applications.…”
Section: Synthetic Biology‐definition and Stakeholdersmentioning
confidence: 99%
“…[1,2] Many valuable compounds have been isolated from Micromonospora in diverse environmental niches, such as turbinmicin, diazepinomicin, diazaquinomicin, and sungeidine. [3][4][5][6] In addition, several clinical used drugs, including gentamicin (antibiotic) and calicheamicin (anticancer), are also produced by Micromonospora species. [7] The recent analysis of biosynthetic gene clusters (BGCs) of Micromonospora isolates further revealed that they have great potential to produce novel natural products.…”
Section: Introductionmentioning
confidence: 99%